1999
DOI: 10.1063/1.371103
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence in silicon oxynitride films

Abstract: We report electroluminescence ͑EL͒ from 50 nm silicon oxynitride films on p-type crystalline silicon substrates in a Au/silicon oxynitride/Si structure. The EL intensity has a peak below 2.45 eV, and is consistent with radiative recombination of injected carriers. The EL is present only in annealed samples, and the emission is similar to the photoluminescence from the same samples. The current-voltage behavior is indicative of space charge-limited current. No polarity or field dependence of the EL peak energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Visible light emission of other oxides has been reported [433] [435], SiON [436], and ITO/SiO [437]. The current band-gap expansion mechanism may provide interpretation for the photoluminescence of these oxides.…”
Section: Blue Light Emission Of Pztmentioning
confidence: 92%
“…Visible light emission of other oxides has been reported [433] [435], SiON [436], and ITO/SiO [437]. The current band-gap expansion mechanism may provide interpretation for the photoluminescence of these oxides.…”
Section: Blue Light Emission Of Pztmentioning
confidence: 92%
“…Some groups reported that the PL in O-type a-SiO x N y was due to radiative recombination between localized band-tail states associated with Si-N bonds which is similar to a-SiN x [32,33], while other groups clarified that the complete picture of PL in silicon oxynitride can be explained by the radiative recombination via both band tail states and luminescent defect states [34]. Besides, it was also suggested that the PL might arise from radiative recombination center consisting of the silicon sub-oxide bonding defects [35][36][37]. Among these various PL models, even though the band tail state and defect state models have gained general consensus, PL mechanisms have still been unclear and even controversial.…”
Section: Introductionmentioning
confidence: 96%
“…So far no rational mechanism could be elucidated. 25,27,40,41 However, in survey XPS spectra of the M-dots (Fig. S2, ESI †) no signal was observed at ca.…”
Section: Resultsmentioning
confidence: 99%